PERFORMANCE ANALYSIS OF PERMANENT FOUNDATION LECTURERS IN IMPLEMENTING THE TASKS OF TRI DHARMA HIGHER EDUCATION (CASE STUDY: HIGH SCHOOL OF TECHNOLOGY NATURAL FENCE CITY - Kasman, Kasman (Perkumpulan Dosen Muda (PDM) Bengkulu, 2021)
A college is an educational institution that responsible to improve human resource. To do it, it is needed professional lecturers, competence and high quality. Lecturer is the main part to make a progress in a college beside the other parts. If those aspects have been done, it means that the purpose of Tri Dharma in a college was achieved. The assessments of lecturer performances are important to do as a measurement of a college in doing Tri Dharma of college. The objective of this research to know the lecturers performances in Sekolah Tinggi Teknologi Pagaralam. The method used was descriptive quantitative by interview for primer data and for secondary data by documentation and observation. The informant of this research was 11 people, they are; lecturer, student, alumnus, staffs, principle and vice principle of Sekolah Tinggi Teknologi Pagaralam. This research refers to four aspects of lecturer duties, quantity of occupation, autonomy of occupation, cooperation, and exact occupation. The result of this research showed that all of the lecturers’ performance in Sekolah Tinggi Teknologi Pagaralam were good. However, it is still necessary to imporve more especially the quantity of lecturer research. Based on the result of this research can be concluded that, Sekolah Tinggi Teknologi Pagaralam still necessary in doing the improvement supervision and motivate to all lecturers especially in doing a research.